HIV-1 Subtype B and C Envelope Glycoprotein based immunogens as preventative vaccines - Grant, Michelle (My University, 2017)
The ability to induce a potent and broadly neutralizing antibody (bNAb) response following vaccination is critical in developing an effective HIV-1 vaccine. To date, no HIV-1 envelope glycoprotein (Env) immunogens have elicited bNAbs in preclinical or human clinical trials. This study compared the antigenicity and immunogenicity of a panel of HIV-1 subtype B and C Env-based immunogens in various immunization regimens in a small animal model. The Env-based immunogens used included matched monomeric (gp120) and trimeric (gp140GCN4(+)) conformations of 6 subtype C Env’s (IN26191, IN25710, IN25925, ZACAP45, ZACAP210 and ZA706010164; all designed during the course of this study), and subtype B stabilized Env derivatives Cyc4OD gp120 cyclic permutant, gp140 cyclic permutant h-CMP V1cyc 144-142, ODECCOBPICS gp120 fragment, VRC01 engrafted scaffold peptides 1WR2 and 1ORC, and DNA (Wt-JRFL-Env, JRFL Env-570D and JRLF Env-SEKS; all obtained from collaborators). The six HIV-1 subtype C Env sequences (IN26191, IN25710, IN25925, ZACAP45, ZACAP210 and ZA706010164) were selected, matched gp120 and gp140GCN4(+) constructs were designed, codon optimized and cloned into a mammalian expression vector. All 12 env constructs were expressed in HEK293T or 293FS cell lines, and the Env purified by lectin affinity chromatography, followed by size exclusion chromatography. Additionally, two domain soluble CD4 (2dCD4) wildtype, folding defective and an S60C mutant were expressed in a bacterial system and purified by nickel affinity chromatography. 2dCD4S60C-liganded Env was prepared, and purified further, as required. The antigenicity of all 12 Env’s was evaluated against 2dCD4 and a panel of bNAbs using surface plasmon resonance (SPR). The immunogenicity of two of these subtype C Env variants (liganded and unliganded to 2dCD4S60C) were subsequently compared to that of the subtype B immunogens in rabbits, using various prime-boost regimens. Rabbit sera were subsequently tested for anti-Env binding antibody titres by enzyme linked immunosorbent assay (ELISA), and neutralization by an in vitro phenotypic neutralization assay against a panel of HIV-1 pseudoviruses. All 12 recombinant Envs were successfully expressed and purified to homogeneity. Binding of all the gp120/gp140GCN4(+) Env variants to 2dCD4 variants (Wt and S60C) confirmed that they were all functional and conformationally intact with an accessible CD4 binding site (CD4bs). Binding to a panel of CD4bs directed bNAbs (IgG1b12, VRC01, HJ16, VRC-CH31, NIH45-46G54W, VRC03) revealed that overall, the trimeric gp140GCN4(+) variants showed higher binding affinities to these bNAbs compared to the matched monomeric gp120, attributed to their resemblance to the native trimer on the viral surface. With the exception of VRC03 and IgG1b12, the Indian Env variants bound with an approximately 10-fold higher affinity compared to the South African Env’s. Overall, nine different immunization regimens were performed. Immunization of rabbits induced high titres of antibodies (Abs) for all the immunogens tested, as determined by ELISA, however, minimal neutralization breadth (against Tier 1 pseudoviruses) was obtained for the Env-only variants for subtype B and C immunogens. Of these, the VRC01 engrafted scaffold peptide (1ORC) showed improved neutralization of the Tier 1 pseudovirus SF162 compared to the other Env only based immunogens. The only promising neutralization results were obtained from rabbits immunized with the Env/2dCD4S60C liganded immunogens that potently neutralized both subtype B and C, Tier 1, 2 and 3 pseudoviruses. This response was improved for the trimeric Env/2dCD4S60C complexes compared to the monomeric ones and was consistently elicited regardless of the Env sequence used. The neutralization response is likely either due to Abs targeting one or more epitopes on 2dCD4 or Env or both. Therefore, the use of CD4 liganded Env immunogens in vaccine design should be investigated further as they provide a promising “Ibalizumab-like” neutralization response. Overall, based on emerging evidence on how the bNAb responses evolve in HIV-1 infected individuals, the findings in this study are promising and lay the groundwork for further testing of these HIV-1 Env based immunogens in various combinations using sequential prime-boost strategies to optimally drive affinity maturation of the appropriate B cell lineages.
A thesis submitted to Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, September 2017.
Keywords: Glycoproteins; Vaccines, Synthetic; HIV-1